Improvement of the Fault Tolerance in IoT Based Positioning Systems by Applying for Redundancy in the Controller Layer (Baghdad Science Journal, 2021)
In recent years, the positioning applications of Internet-of-Things (IoT) based systems have grown increasingly popular, and are found to be useful in tracking the daily activities of children, the elderly and vehicle tracking. It can be argued that the data obtained from GPS based systems may contain error, hence taking these factors into account, the proposed method for this study is based on the application of IoT-based positioning and the replacement of using IoT instead of GPS.  This cannot, however, be a reason for not using the GPS, and in order to enhance the reliability, a parallel combination of the modern system and traditional methods simultaneously can be applied. Although GPS signals can only be accessed in open spaces, GPS devices are error-prone primarily when the receiver is located in an urban-canyons area, due to congestion and the possible interference. The outcome presents a redundancy-based model for improving the fault tolerance of IoT-based positioning systems. The simulation results show a 22.5% improvement in the fault tolerance of the IoT-based positioning system after applying the proposed validation mechanism, and a 77.4% improvement in this tolerance after applying for a more expensive module redundancy.